UFOs, ETs, and Alien Abductions: A Scientist Looks at the Evidence by Don Donderi - Bullard, Eddie (Journal of Scientific Exploration, 2014)
Many books about UFOs appear each year, yet few of these books are worth reading; UFOs, ETs, and Alien Abductions is one of those few. The author, Don Donderi, holds a doctorate in psychology and spent most of his career at McGill University in Montreal as a professor, dean, and researcher. His specialties are human visual perception and memory, with several books and more than one hundred research papers and technical reports to his credit. He began to read about UFOs when he was ten years old. The interest has stayed with him throughout his life and motivated him to investigate several sightings as the opportunities arose. In 1968 he participated in a review of occupant cases as a consultant for the National Investigations Committee on Aerial Phenomena (NICAP), then the leading U.S. civilian UFO investigations organization. In the 1990s, when abductions dominated ufology, he consulted on how to interpret the results of a Roper Poll designed to uncover the prevalence of abduction-like experiences in the general public, and participated in major meetings such as the 1992 Abduction Study Conference held at MIT. He further lent his psychological expertise to a personality test for separating simulated abduction claims from honest experiential reports, and to an experiment that compared symbols reported by abductees with symbols imagined by non-abductees.